Community Participation in the Simultaneous Village Head Election in Sinjai Timur District - Yudarti; Hartati Malkab; Usnidah Umar; Faradina, Faradina; Muhlis Hajar Adiputra (Tinta Emas Institute, 2023)
The research focused on assessing community participation in the simultaneous village head election in East Sinjai sub-district, employing a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. Findings revealed various facets of community involvement. Firstly, participation in generating ideas was limited, as many believed their role began only during the voting process. Secondly, active participation in campaigning for worthy candidates proved effective, reflecting community engagement in endorsing potential leaders. Thirdly, time-based participation was insufficient, as individuals returning to their villages often failed to align their visits with the election schedule. The fourth aspect highlighted that community motivation to vote stemmed from the awareness that abstention could hinder the progress of their chosen candidate, fostering a desire for positive change. Conversely, factors hindering voting included familial dissatisfaction with candidates, age-related concerns, and significant migration during election periods. Notably, the study indicated an overall insufficient level of community participation in the 2022 simultaneous village head elections, with 866 individuals from Biroro Village and Patalassang Village not exercising their voting rights as registered on the Permanent Voter List. These findings underscore the need for targeted strategies to enhance community involvement, addressing specific barriers identified in the study for future electoral processes.